2015
DOI: 10.1093/cvr/cvv108
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of ANKRD1 disrupts sarcomeric ERK-GATA4 signal transduction and abrogates phenylephrine-induced cardiomyocyte hypertrophy

Abstract: Our study reveals a novel role for ANKRD1 as a selective regulator of PE-induced signalling whereby ANKRD1 recruits and localizes GATA4 and ERK1/2 in a sarcomeric macro-molecular complex to enhance GATA4 phosphorylation with subsequent nuclear translocation of the ANKRD1 complex to induce hypertrophic gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 40 publications
1
63
0
Order By: Relevance
“…MARP1 binds to titin's elastic N2A region (Figure 6). MARP proteins have been proposed to be stretch responsive9 and have been implicated in hypertrophy signalling, through interaction with the Erk‐GATA4 complex 48. As following UDD MARP1 shows no evidence of nuclear localization (Figure 6A–F), therefore interaction with GATA4 is unlikely.…”
Section: Discussionmentioning
confidence: 97%
“…MARP1 binds to titin's elastic N2A region (Figure 6). MARP proteins have been proposed to be stretch responsive9 and have been implicated in hypertrophy signalling, through interaction with the Erk‐GATA4 complex 48. As following UDD MARP1 shows no evidence of nuclear localization (Figure 6A–F), therefore interaction with GATA4 is unlikely.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies demonstrated that the activity of C/EBP β, c-Fos and HIF-1αis also regulated by posttranslational modification caused by phosphorylation by different kinases, such as MAPK, cdc2, PKA and PKC1617484950. Previous studies targeted the effects of ERK1/2 pathways on GPR91-dependent VEGF expression in the retinas of streptozotocin-induced diabetic rats7.…”
Section: Discussionmentioning
confidence: 99%
“…Since we have validated the protective roles of ACE3 in response to Ang II‐ and pressure overload‐induced cardiac hypertrophy, it has significance to test whether ACE3 can also affect other types of cardiac hypertrophy, such as the adrenergic receptor‐induced cardiac hypertrophy. Among the multiple signaling pathways that activated by the adrenergic receptors, a large body of evidence has showed the essential roles of the ERK1/2 signaling during different adrenergic receptor‐induced hypertrophic response 25, 26. As we have demonstrated the anti‐hypertrophic effects of ACE3 are mainly depend on inhibition of the MEK‐ERK1/2 signaling, it is likely that ACE3 can also function as a negative regulator in adrenergic receptor‐induced hypertrophy.…”
Section: Discussionmentioning
confidence: 69%